Diallel analysis for yield and yield attributing traits in capsicum (Capsicum annuum L. var grossum Sendt) - Pandey, Vandna; Chura, Abhishekh; Pandey, HK; Meena, HS; Arya, MC; Ahmed, Z (Vegetable Science, 2012)
The present investigation was carried out to study heterosis and combining ability for yield and its yield attributing traits in capsicum. The experimental material consisted of twelve parents and 66 F1S produced in diallel mating design excluding reciprocals. Analysis of variance for combining ability exhibited the significance for gca and sca effects of all the characters studied. The remarkable heterosis for yield and its yield attributing traits was also observed. The high performing crosses for all the characters studied showed that in general these crosses involved high x high, low x low, high x low and low x high general combiners. The low x low crosses giving high sca value may be due to genetic diversity of the parents and non allelic interactions. On the basis of heterosis and sca effects, Feroj x SP-6, DARL-70 x DARL-71, Capsicum Violet x California Wonder SP-6 x Dark Green and Feroj x DARL-71 were identified as promising hybrids.